Continuation of positively determined functions on the ball in the infinite sphere - Kuznetsova О. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
It is shown that every positive definite function on a ball in an infinite-dimensional sphere can be extended to a positive definite function on the whole sphere, and the extension is moreover unique.